PENGUKURAN KINERJA PADA PEMERINTAHAN DAERAH: TELAAH FAKTOR INSTITUSIONAL - Rabina Laila (2021)
The Implementation of performance measurement in Indonesia has not yet been fully implemented. Report from the belitungtimurkab.go.id page, the State Administration Agency assessed that there were still many weaknesses and shortcomings of the State Civil Apparatus in compilling and making Government Agency Performance Accountability Reports (GAPAR). This is because the reports made by the State Civil Apparatus do not inform the success of agencies using performance measurement, but rather report more on the activities they have carried out and do not focus on improving performance in the previous period. This research was determine the effect of institutional factors, wich are management innovation, resources, legislative mandate, management innovation, and reward/incentive on performance measurement. The sample used in this reaserch amounted to 64 samples who came from the Head of Subdivision Planning with her staff at the Regional Apparatus Organization in the South Tangerang City Covernment with a questionnaire instrument. The analysis technique used is Structural Equation Modelling (SEM), using the Smart Partial Least Square version 3.0. the result of this study indicate that management commintment and legislative mandate significantly influence performance measument. While resources, management innovation, and reward/incentive does not significantly influence performance measument.